(untitled) (CIPEEX, 2022)
&NBSP;THE PRESENT STUDY SEEKS TO ADDRESS A REALITY THAT IS INCREASINGLY EVIDENT IN THE GLOBAL CONTEXT, IN WHICH AGING IS GAINING MORE SPACE AND PARTICIPATION IN EPIDEMIOLOGICAL INDICATORS. SINCE LIFE EXPECTANCY, MAINLY IN DEVELOPED AND DEVELOPING COUNTRIES, SUCH AS BRAZIL, HAS BEEN EXPANDING, POPULATION GROWTH HAS BEEN NOTABLY ASSOCIATED WITH THE VIOLENCE PERPETRATED AGAINST SENIOR CITIZENS, CHARACTERIZING WHAT IS KNOWN AS €ŒVIOLENCE AGAINST THE ELDERLY€, WHICH INVOLVES ACTS THAT CULMINATE IN THE LOSS OF THEIR QUALITY OF LIFE. DUE TO THE TERRITORIAL AND CULTURAL EXTENSION OF BRAZIL, IT IS EXPECTED THAT THERE WILL BE DIFFERENT EPIDEMIOLOGICAL PROFILES IN EACH REGION WITH REGARD TO THE VIOLENCE AGAINST THE ELDERLY.